The Use of Model to Determine Ecological Variables Responsible for Soil Organic Carbon Sequestration in Derived Savanna Soils of Southwestern Nigeria - E. O. Adeosun; B. S. Awe; P. O. Ajewole (Archives of Current Research International, 2018)
The objective of this study is to determine the influence of ecological variables on the stock of carbon using a stepwise regression model. The study was carried out at Itapaji, a farming community in the derived savanna zone in Ekiti North Senatorial District. Soil samples were collected from the identified horizons, and the profiles were described following the standard method. Data obtained were analysed using stepwise multiple regression analysis with the aid of SPSS 17. 0. A model that identifies the significant ecological variables that explained increased variability in the SOC sequestration of the study area was developed The model results are expected to be a guide for predicting SOC storage in different soil types with similar land types, agro-ecological conditions, and vegetation types. It is recommended that management practices such as cover crop, residue retention, zero tillage, appropriate use of fertiliser, long fallow period, controlled bush burning, and appropriate management technique suitable for the different topographic land type will enhance SOC sequestration in the study area.